2003
DOI: 10.4049/jimmunol.170.4.1806
|View full text |Cite
|
Sign up to set email alerts
|

Suppressive DNA Vaccination in Myelin Oligodendrocyte Glycoprotein Peptide-Induced Experimental Autoimmune Encephalomyelitis Involves a T1-Biased Immune Response

Abstract: Vaccination with DNA encoding a myelin basic protein peptide suppresses Lewis rat experimental autoimmune encephalomyelitis (EAE) induced with the same peptide. Additional myelin proteins, such as myelin oligodendrocyte glycoprotein (MOG), may be important in multiple sclerosis. Here we demonstrate that DNA vaccination also suppresses MOG peptide-induced EAE. MOG91–108 is encephalitogenic in DA rats and MHC-congenic LEW.1AV1 (RT1av1) and LEW.1N (RT1n) rats. We examined the effects of DNA vaccines encoding MOG9… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
49
0

Year Published

2003
2003
2009
2009

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 42 publications
(53 citation statements)
references
References 35 publications
4
49
0
Order By: Relevance
“…Gene therapy has not yet been attempted in MS, but there have been a number of studies in EAE that have invariably shown some level of efficacy at inhibiting the disease (Table 1), although in many cases this has only been an amelioration rather than elimination of disease. As the majority of the CNS is postmitotic, this puts constraints on the nature of the vector that can be used, and to date administration of plasmid DNA, [32][33][34][35][36][37][38][39][40][41] viral infection, [42][43][44][45][46][47][48][49][50][51][52][53] and retrovirally transduced cell (RVC)-carriers 47,[54][55][56][57][58][59][60][61][62][63] have been investigated in EAE (Table 1). These have largely focused on inhibition of the immune response either applied centrally to target the local pathological events within the CNS or peripherally administered to inhibit: initial sensitization, the activities of circulating cells or perivascular events in areas of local BBB breakdown.…”
Section: Gene Therapy In Autoimmune Demyelinating Diseasementioning
confidence: 99%
See 4 more Smart Citations
“…Gene therapy has not yet been attempted in MS, but there have been a number of studies in EAE that have invariably shown some level of efficacy at inhibiting the disease (Table 1), although in many cases this has only been an amelioration rather than elimination of disease. As the majority of the CNS is postmitotic, this puts constraints on the nature of the vector that can be used, and to date administration of plasmid DNA, [32][33][34][35][36][37][38][39][40][41] viral infection, [42][43][44][45][46][47][48][49][50][51][52][53] and retrovirally transduced cell (RVC)-carriers 47,[54][55][56][57][58][59][60][61][62][63] have been investigated in EAE (Table 1). These have largely focused on inhibition of the immune response either applied centrally to target the local pathological events within the CNS or peripherally administered to inhibit: initial sensitization, the activities of circulating cells or perivascular events in areas of local BBB breakdown.…”
Section: Gene Therapy In Autoimmune Demyelinating Diseasementioning
confidence: 99%
“…In addition, some studies have attempted to promote repair or inhibition of the demyelination process. 40,44,49,57,61 Cytokines are dynamically expressed as lesions evolve and resolve [12][13][14][15][16] and are of major importance in the development and control of autoimmunity. 12 Many studies in EAE focus on the use of knockout mice.…”
Section: Gene Therapy In Autoimmune Demyelinating Diseasementioning
confidence: 99%
See 3 more Smart Citations